Goiter and Laryngeal Sensory Neuropathy. (29th May 2013) - Hamdan, Abdul Latif; Jabour, Jad; Azar, Sami T.
Abstract : Objective . Examining the prevalence of laryngeal sensory neuropathy (LSN) in goiter patients versus a control group. Study Design . Cross-sectional study. Methods . 33 Goiter patients were enrolled versus 25 age-matched controls. TSH levels, size of thyroid gland, and presence or absence of thyroid nodules were reported. Subjects were asked about the presence or absence of any of the following symptoms: cough, globus pharyngeus, and/or throat clearing that persistented for more than 6 weeks. The presence of one or more of these symptoms for at least six weeks in the absence of LPRD, allergy, asthma, ACE inhibitor intake, and psychogenic disorder was defined as LSN. Results . For goitrous patients mean age (years) was (41.73 ± 9.47 ) versus (37.44 ± 10.89 ) for controls. 82% goitrous patients had known nodules and 27% carried a simultaneous diagnosis of hypothyroidism. Among those with documented size (61%), mean total thyroid volume was 26.996 ± 14.852 cm 3, with a range from 9.430 to 67.022 cm 3 . The overall prevalence of LSN among goitrous patients was 42% versus 12% among controls (P = 0.0187 ). There was no correlation between LSN, size of thyroid gland, and TSH level. Conclusion . The prevalence of LSN in goitrous patients is significantly higher than that in a nongoitrous population.